NF-κB Regulation by Gut Microbiota Decides Homeostasis or Disease Outcome During Ageing - Zhang, Shuning; Paul, Soumyajeet; Kundu, Parag (Frontiers in Cell and Developmental Biology, 2022)
Human beings and their indigenous microbial communities have coexisted for centuries, which led to the development of co-evolutionary mechanisms of communication and cooperation. Such communication machineries are governed by sophisticated multi-step feedback loops, which typically begin with the recognition of microbes by pattern recognition receptors (PRRs), followed by a host transcriptional response leading to the release of effector molecules. Our gastrointestinal tract being the main platform for this interaction, a variety of host intestinal cells tightly regulate these loops to establish tolerance towards the microbial communities of the gut and maintain homeostasis. The transcription factor, nuclear factor kappa B (NF-κB) is an integral component of such a communication apparatus, which plays a critical role in determining the state of homeostasis or inflammation associated with dysbiosis in the host. Here we outline the crucial role of NF-κB in host response to microbial cues in the context of ageing and associated diseases.